Simulation Analysis of Beam Intensity Attenuation Patterns and Source Depth Estimation Using a Vertical Long Line Array - WANG, Hao; ZHENG, Guangying; ZHU, Fangwei; YANG, Xiaohong; ZHANG, Shuaishuai; GUO, Xiaowei (Archives of Acoustics, 2025)
In the deep-water reliable acoustic path (RAP), when estimating target depth using a vertical array, a large-aperture array can enhance the extraction of the acoustic field interference structure under low signal-to-noise ratio (SNR). However, this operation introduces slow envelope modulation (the envelope amplitude of peak beam intensity decreases with frequency) to the broadband acoustic field interference pattern, significantly degrading the performance of estimating the source depth. The Kraken normal-mode model can accurately calculate low-frequency sound fields in deep-water environments. This paper uses this tool to find that, in the deep-water direct arrival zone (DAZ), the peak beam intensity output of a vertical linear array varies across a broadband frequency range, exhibiting a pattern combining periodic changes of Lloyd’s mirror interference and inherent envelope attenuation changes. The physical mechanism of envelope attenuation is explained through both theoretical derivation and simulation analysis, key factors affecting the envelope-attenuation pattern are clarified, and the impact of beam-intensity envelope attenuation on the depth-estimation method based on matched beam intensity processing (MBIP) is pointed out. Based on this, a modified target depth estimation method of matched beam intensity processing (M-MBIP) that contains an attenuation coefficient is proposed, and its effectiveness is verified through simulated data.